PERTARUNGAN PEMIKIRAN ANTARA KH. SHINWANI ADRA'I DAN ULAMA ASWAJA LOKAL DI MADURA: ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH - Rista Irawati; Agik Nur Efendi; Mohammad Ali Al Humaidy; Himatus Sya’adah; Syukron Affani (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
Religious conflict between KH. Shinwani Adra’i and Aswaja ulama in Madura reflects tensions between a text-based orientation toward ritual purification and socio-religious practices that have long been embedded in local culture, particularly devotional traditions such as tahlil and maulid. This study aims to uncover the roots of these tensions and to explain how discourses of difference can be transformed into narratives of peace. The research employs a qualitative approach using Norman Fairclough’s Critical Discourse Analysis model. Data were collected through a literature-based study of YouTube sermons, responses from local kiai, and relevant academic references, then analyzed across three dimensions: text, discursive practice, and social practice. The findings indicate that the conflict arises not only from theological differences but also from competition over the legitimacy of religious authority in digital spaces, which amplifies the conflict’s resonance. However, scholarly clarification and pesantren-based mediation are able to reconstruct the meaning of “difference” as a potential resource for social learning. This study contributes to scholarship on local religious authority and proposes a discourse-based framework for reconciliation.